Novel mutation in exon11 of PRKCG (SCA14): A case report - Sun, Rong; Tang, Xiang; Cao, Xueqin; Shao, Xinyu; Sun, Hong (Frontiers in Genetics, 2023)
Abstract: Introduction: PRKCG mutations have been implicated in the pathogenesis of spinocerebellar ataxia type 14 (SCA14), which is a rare autosomal dominant disease marked by cerebellar degeneration, dysarthria, and nystagmus. Until now, there has been no report of patients with mutations of c.1232G>C worldwide. Case description: We reported a case of a 30-year-old Chinese man with episodic dystaxia, speech disorder, and cognitive impairment; however, his father exclusively exhibited a speech disorder regardless of the same mutation. Whole exome sequencing revealed the heterozygous c.1232G>C (p.G411A) variant of PRKCG. Conclusion: This case reports an extended genotype and phenotype of SCA14, emphasizing the importance of gene sequencing in patients with spinocerebellar ataxia.